1998
DOI: 10.3168/jds.s0022-0302(98)75664-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Yucca shidigera Extract and Soluble Protein on Performance of Cows and Concentrations of Urea Nitrogen in Plasma and Milk

Abstract: Twelve multiparous Holstein cows averaging 122 d postpartum were used in a replicated Latin square design with 21-d periods. Cows were fed diets containing either low or high soluble protein supplemented with 0 or 9 g/d of Yucca shidigera extract per cow. Dry matter intake and yields of milk, fat, 3.5% fat-corrected milk, and total solids were not affected by treatment. High soluble protein increased percentages of fat and total solids in milk but decreased percentages of crude protein and true protein in milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 14 publications
6
32
0
3
Order By: Relevance
“…There are reports that milk yields and the composition of milk from moderate-or high-yielding cows (20 -30 kg/d) are not improved by inclusion of Yucca or Quillaja extract in diets containing 10 to 20 % crude protein (25,29,30,36,37,40,42) . Even supplementation of diets containing less than 10 % protein with Yucca saponins (0·1 g/kg) did not affect milk production (119) .…”
Section: Effects Of Saponins On Ruminant Performancementioning
confidence: 99%
See 2 more Smart Citations
“…There are reports that milk yields and the composition of milk from moderate-or high-yielding cows (20 -30 kg/d) are not improved by inclusion of Yucca or Quillaja extract in diets containing 10 to 20 % crude protein (25,29,30,36,37,40,42) . Even supplementation of diets containing less than 10 % protein with Yucca saponins (0·1 g/kg) did not affect milk production (119) .…”
Section: Effects Of Saponins On Ruminant Performancementioning
confidence: 99%
“…Sapindus saponaria (27) and Yucca extract (42) included in concentrate diets did not significantly reduce rumen ammonia concentrations, although it should be noted that the Yucca extract did not affect rumen protozoal numbers either. In studies with dairy cows, inclusion of sarsaponins up to 77 parts per million (ppm) of diet (29,33) , 9 g/d (36) , 8 g/d (40) and 10 g of Yucca whole plant (equivalent to 0·6 g saponins/kg DM) or 10 g Quillaja whole plant (equivalent to 0·3 g saponins/kg DM) (25) did not influence ammonia concentrations in the rumen, probably due to low concentrations of saponins inclusion in the diets. Valdez et al (29) and Hess et al (27) have reported that by decreasing protozoal numbers slightly, saponins increased bacterial numbers, which may explain why saponin treatments are not always associated with reduced rumen ammonia concentrations.…”
Section: Nitrogen Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…This parameter is positively correlated with the ingestion of nitrogen by the animal (ROSELER et. al., 1993;HENNESSY et al, 1995;VALADARES et al, 1997;MOSCARDINI et al, 1998;CANNAS et al, 1998;WILSON;OVERTON;CLARK, 1998). Thus, the decrease in the levels of urea-N in the blood may be related to the modification of the fractionation of the nitrogen compounds in the diets due to the inclusion of the licury cake (Table 4); the reduction of the protein fraction A and a rapid degradability and increase of the fractions B3 and C, which are slow degrading and not degradable, respectively, was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Segundo Clark et al (1992), a disponibilidade de energia e N são fatores limitantes para o crescimento microbiano. De acordo com Kauffman e St-Pierre (2001), com aumento de amônia ruminal, ocorre aumento da concentração sanguínea de uréia e , conseqüentemente, sua difusão para o leite, ou seja, a uréia ao ser sintetizada no fígado é transportada para o sangue (filtrada no rim e excretada na urina ou reciclada para o rúmen) e glândula mamária (excretada no leite) (Wilson et al, 1998), o que é coerente com a maior concentração de NUP obtida (Tabela 5).…”
Section: (%)unclassified